THE FDI-INCOME-ENERGY-ENVIRONMENT NEXUS AND FISCAL POLICY UNDER CARBON NEUTRALITY REGULATION: EVIDENCE FROM SIX EAST ASIAN ECONOMIES - Sinmee, Sarunchana; Sinnarong, Nirote; Nunthasen, Ke; Nunthasen , Waraporn; Saensan , Thanakorn (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This research investigated the complex relationship between carbon dioxide emissions and economic determinants in East Asian economies, with particular emphasis on the impact of foreign direct investment (FDI), energy consumption patterns, gross domestic product per capita, and governmental fiscal policy instruments on CO₂ emissions during the period between 2001 and 2023. The study employed a quantitative methodological framework utilizing longitudinal panel data collected from six distinct economic jurisdictions: Japan, South Korea, Singapore, China, Indonesia, and Thailand. Secondary data were systematically extracted from the World Bank database, with analytical procedures incorporating Panel Unit Root Tests and Feasible Generalized Least Squares (FGLS) to address heteroskedasticity and autocorrelation concerns inherent in cross-sectional time-series data. The empirical findings demonstrated that energy consumption emerged as the predominant driver of carbon dioxide emissions, exhibiting a robust positive coefficient of 0.656 (p<0.01) across the examined economies. Evidence supporting the Environmental Kuznets Curve hypothesis, which postulates an inverted U-shaped relationship between economic development and environmental degradation, was observed exclusively in Japan, with statistically significant GDP and GDP² coefficients of 137.0 and -6.316 (p<0.05), respectively. Concerning fiscal policy instruments, taxation mechanisms demonstrated efficacy in mitigating CO₂ emissions only in China and Indonesia, with respective coefficients of -0.036 and -0.207 (p<0.1). Interestingly, foreign direct investment did not exhibit statistically significant effects on emission levels across the sampled economies. These nuanced findings underscore policymakers' need to design and implement differentiated environmental strategies that acknowledge and accommodate the heterogeneous stages of economic development across East Asian economies. The results suggest that a one-size-fits-all approach to environmental policy formulation would be suboptimal given the diverse relationships between economic factors and carbon emissions observed across different jurisdictions within the region.